2016
DOI: 10.3233/nre-161305
|View full text |Cite
|
Sign up to set email alerts
|

Dysarthria as a predictor of dysphagia following stroke

Abstract: A comprehensive evaluation of dysphagia, aphasia, and dysarthria are important to improve clinical outcome following stroke. The identification of dysarthria as a predictor of dysphagia can help identify risk for dysphagia in stroke and assist in the therapeutic process of swallowing problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…With FBAS administration, valuable clinical information is further collected with regards to functional language comprehension associated with a patient's ability to follow a verbal command as well as dysarthria, with the latter proven to be a strong predictive factor for both dysphagia and aspiration risk. 3,[45][46][47] Our protocol includes a water swallow trial (WST) to aid in recognition of aspiration risk in acute stroke as do most valid swallowing screening tests 7,8,45 and acknowledges as failure criteria already established sensitive indicators for aspiration. 5,10,18,40,46 A recent meta-analysis 10 revealed that when administering single sips of small and large volumes, the WST offers the best evidence for accurately discriminating patients who are aspirating.…”
Section: Discussionmentioning
confidence: 99%
“…With FBAS administration, valuable clinical information is further collected with regards to functional language comprehension associated with a patient's ability to follow a verbal command as well as dysarthria, with the latter proven to be a strong predictive factor for both dysphagia and aspiration risk. 3,[45][46][47] Our protocol includes a water swallow trial (WST) to aid in recognition of aspiration risk in acute stroke as do most valid swallowing screening tests 7,8,45 and acknowledges as failure criteria already established sensitive indicators for aspiration. 5,10,18,40,46 A recent meta-analysis 10 revealed that when administering single sips of small and large volumes, the WST offers the best evidence for accurately discriminating patients who are aspirating.…”
Section: Discussionmentioning
confidence: 99%
“…Common neurological impairments include facial paresis as well as tongue, mandibular, pharyngeal, and laryngeal dysfunction. In isolation, or in various combinations these symptoms can lead to dysphagia, dysarthria, malnutrition, dehydration, airway obstruction, and death (Bahia, Mourão, & Chun, 2016;Daniels, Brailey, Priestly, Weisberg, & Foundas, 1998;Daniels & Foundas, 1997;Galovic et al, 2013;Kumral, Celebisoy, Celebisoy, Canbaz, & Calli, 2007;Leder & Espinosa, 2002;Miller, 1999Miller, , 2008Nunes et al, 2012;Smithard et al, 1996;Urban, Hopf, Fleischer, Zorowka, & M€ uller-Forell, 1997;Urban, Wicht, Hopf, Fleischer, & Nickel, 1999). Underlying these severe and debilitating clinical consequences is the presumed disruption of descending axons destined for the brainstem reticular formation, and corticobulbar fibers directly innervating cranial nerve motor nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the consequences of ECA, when articulation, breathing, voice, rhythm and fluency (30) can be impaired. In TBI, dysarthrias are present in approximately 45% of cases (31) . In SCP, hyperreflexia and exaggerated increase in muscle tone occur, with reduction of voluntary movements (13) .…”
Section: Discussionmentioning
confidence: 99%